Electron Acceptor Selection for Enhanced Bioremediation of Non-chlorinated Hydrocarbons - Elkins, Brad; Yuncu, Bolgen (Águas Subterrâneas, 2019)
Replenishment of electron acceptors in the subsurface is a common method to stimulate biodegradation of non-chlorinated hydrocarbons in groundwater. Two widely used products are calcium-based peroxides for aerobic degradation and sulfate-based salts for anaerobic degradation. What design parameters should a consultant consider in selecting from multiple electron acceptors? A small consulting firm was responsible for addressing BTEX (benzene, toluene, ethylbenzene, and xylenes) contamination at a former gas station site. The challenge was to select the appropriate electron acceptor that could cost-effectively stimulate bioactivity and reduce contaminant concentrations that had remained above the state MCL for over a decade. Of the electron acceptors considered, EAS™ (Electron Acceptor Solution) was selected to enhance anaerobic biodegradation of BTEX under established sulfate-reducing conditions. During the pilot study, 52.5 gallons of EAS™ was introduced into the former UST pit area (via a single injection well) and samples were collected at several downgradient monitoring wells.